Inventory planning with innovation a cost focus - Sharma, Sanjay (CRC Press, 2021)
"Discussing innovation efforts and different factors including the type and size of an organization, nature, and boundary of innovation, and area and scope of work, this text will be a valuable resource for senior undergraduate, graduate students, and professionals in the field of industrial engineering, production engineering, and manufacturing science. It further covers important concepts such as related expenditure, time consideration, and related total cost planning in a comprehensive manner"--
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on April 26, 2021)
Keywords: Inventory control; Gestion des stocks; inventorying; TECHNOLOGY; Manufacturing; TECHNOLOGY; Quality Control